Composite polyurethane film capable of preventing fouling and adsorbing bivalent copper ions in seawater as well as preparation method and application of composite polyurethane film

By copolymerizing tannin acid and collagen with polyurethane, a composite polyurethane film with anti-fouling and adsorbing seawater divalent copper ions was prepared, which solved the environmental pollution problem of copper ions released by traditional anti-fouling agents, and improved the stability and adsorption performance of the material.

CN119588324APending Publication Date: 2025-03-11HAINAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411790172.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Traditional antifoulants release divalent copper ions in seawater, resulting in marine environmental pollution. At the same time, existing copper adsorbent materials have single functions, high costs or risk of environmental pollution.

Method used

A composite polyurethane film with antifouling and adsorbing seawater divalent copper ions was prepared by copolymerizing tannin acid and collagen.

Benefits of technology

This composite polyurethane film not only has good anti-fouling performance, but also can effectively adsorb divalent copper ions in seawater, reducing the risk of pollution in the marine environment, and at the same time solves the problem of poor water stability of tannin acid and improves the stability and service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005175127790000071
    Figure BDA0005175127790000071
  • Figure BDA0005175127790000072
    Figure BDA0005175127790000072
  • Figure BDA0005175127790000073
    Figure BDA0005175127790000073
Patent Text Reader

Abstract

The invention provides a composite polyurethane film capable of preventing fouling and adsorbing bivalent copper ions in seawater and a preparation method and application thereof.The method comprises the steps that firstly, polyurethane is prepared through a high-molecular organic polymerization reaction, and a tannic acid / collagen compound is used for modifying the polyurethane; the adsorption performance of the original polyurethane is improved, and meanwhile, the antifouling function is given to the polyurethane. Besides, tannic acid is poor in stability in water and easy to dissolve in water, however, tannic acid and collagen are co-precipitated in water, and then the precipitate is grafted to polyurethane, so that the problem of water stability of tannic acid is solved, and meanwhile, because collagen is rich in amino groups, adsorption of bivalent copper ions can be further improved. The preparation method has the advantages that the operation is simple and convenient, the production efficiency is high, the raw materials are easy to obtain and the like, a feasible technical route is provided for industrial production, and a new thought and a new method are provided for reducing the concentration of bivalent copper ions in a marine environment and reducing marine biofouling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of marine heavy metal adsorption materials and marine antifouling materials, and in particular to a composite polyurethane film having the functions of antifouling and adsorption of divalent copper ions in seawater, and a preparation method and application thereof. Background Art

[0002] There are a large number of pollutants in the marine environment, among which heavy metal ions (such as copper ions, Cu(Ⅱ)) are one of the main pollutants. These heavy metal ions are not only harmful to marine life, but also have long-term effects on human health and the environment. Due to the extensive use of traditional antifouling agents, such as CuO, the antifouling paint originally coated on the hull is immersed in seawater for a long time, causing Cu(Ⅱ) to gradually release into the seawater, resulting in an increase in the concentration of Cu(Ⅱ) in the sea area, which has an adverse impact on the marine environment. Marine antifouling is an important research field. Biological fouling (such as marine biological attachment) can reduce the performance of ships, marine structures and other equipment, increase maintenance costs, and have a negative impact on the environment. Traditional antifouling coatings usually contain toxic chemicals that may cause secondary pollution to the environment.

[0003] As a bio-derived raw material, tannic acid has the advantages of being natural and renewable, widely available, and inexpensive. The average functionality of the hydroxyl group in its molecular structure is 15, and the multifunctional -OH makes it possible for tannic acid to be used as an internal crosslinking agent to modify polyurethane. At the same time, tannic acid is similar in structure to hyperbranched polyesters, with 5 branches attached to the pyranose heterocycle; 25 -OH and 10 ester chains, which can replace the synthesized polyester polyols, not only improving the mechanical properties and medium resistance of polyurethane films, but also reducing production costs. In addition, tannic acid is a natural polyphenol compound with strong metal chelating ability and antioxidant properties. It can form stable complexes with metal ions, thereby effectively adsorbing heavy metal ions. Tannic acid also has certain antibacterial and antifouling effects, but it is easily soluble in water and has poor stability.

[0004] Collagen is a natural biomacromolecule with good biocompatibility and degradability. It can coprecipitate with tannic acid in water to solve the problem that tannic acid is easily soluble in water. In addition, collagen can provide a good matrix, which helps to improve the mechanical properties and stability of the composite material. Collagen itself also has a certain ability to adsorb metal ions. Polyurethane is a high-performance polymer material with good mechanical strength, wear resistance and elasticity. It can give polyurethane film excellent mechanical properties.

[0005] Chinese patent literature discloses a "method for preparing a copper adsorbent", and its application publication number is CN106040193A. This method introduces diene ketone acetate, hexafluoroacetylacetone-cyclooctadiene copper, and 1-vinyl-3-ethylimidazole bistrifluoromethanesulfonyl imide salt into vinylidene chloride polymerization to prepare the copper adsorbent. However, the reagents used in this method are relatively expensive, and the prepared material has a single function. Therefore, it is necessary to study and develop a copper adsorbent with rich usage and low price.

[0006] Chinese patent literature discloses "a magnetic ceramsite adsorbent and preparation method for removing heavy metal copper ions from water", and its application publication number is CN115608340A. This method first pre-treats the dehydrated printing and dyeing sludge, and uses a co-precipitation method to prepare magnetic clay, which is then calcined to obtain ceramsite. Although this method is technically simple to prepare, the raw material printing and dyeing sludge used has complex components and may cause secondary pollution to the environment. Therefore, it is of great significance to prepare a pollution-free copper adsorbent.

[0007] In summary, it is of great significance to study a material with easy-to-obtain, cheap raw materials, simple preparation process, and the dual functions of adsorbing heavy metal ions in seawater and marine antifouling. Summary of the invention

[0008] In view of this, the present invention proposes a composite polyurethane membrane having both antifouling and adsorption properties for divalent copper ions in seawater and a preparation method and application thereof to solve the above problems.

[0009] The technical solution of the present invention is achieved as follows: A method for preparing a composite polyurethane film having both antifouling and adsorption of divalent copper ions in seawater comprises the following steps:

[0010] S1. Blending tannic acid, collagen and deionized water to obtain a precipitate A;

[0011] S2, copolymerizing polytetrahydrofuran and isophorone diisocyanate to obtain polyurethane B;

[0012] S3, copolymerizing the prepared precipitate A with polyurethane B to obtain tannic acid / collagen composite polyurethane;

[0013] S4. Pour the prepared tannic acid / collagen composite polyurethane into a polytetrafluoroethylene mold while it is hot, dry it naturally and then dry it in an oven to obtain a tannic acid / collagen composite polyurethane film.

[0014] Furthermore, a method for preparing a composite polyurethane membrane having both antifouling and adsorption of divalent copper ions in seawater specifically comprises the following steps:

[0015] S1. Mix tannic acid and collagen in deionized water, wherein the mass volume ratio of tannic acid, collagen and deionized water is (10-15):(10-15):100. During stirring, the pH is controlled to be 7.0 so that the tannic acid and collagen react fully to obtain a precipitate A.

[0016] S2. Add isophorone diisocyanate dropwise to polytetrahydrofuran at room temperature, continue stirring to react, and maintain the temperature at 80-85° C. after heating for 2-2.5 hours to obtain polyurethane B;

[0017] S3, continue to add chain extender, catalyst and precipitate A to polyurethane B, reflux and stir to react, and keep the temperature at 60-70°C for 5-7h to obtain tannic acid / collagen composite polyurethane;

[0018] S4, pouring the tannic acid / collagen composite polyurethane of step S3 into a polytetrafluoroethylene mold while it is hot, leaving it at room temperature for two days to dry into a film, and then putting the obtained film into an oven and drying it at 40-60° C. for 20-30 hours to obtain a composite polyurethane film.

[0019] Furthermore, the stirring rate of S1 is 100-150 rpm, and the stirring time is 1-1.2 h.

[0020] Furthermore, the stirring rate of S2 is 200-400 rpm, and the heating rate is 3-5°C / min.

[0021] Furthermore, the stirring rate of S3 is 200-400 rpm, and the heating rate is 1-3°C / min.

[0022] Furthermore, a composite polyurethane membrane having both antifouling and adsorption properties of divalent copper ions in seawater is prepared by the above-mentioned preparation method.

[0023] Furthermore, a composite polyurethane membrane having both antifouling and adsorption properties for divalent copper ions in seawater comprises the following raw materials in weight percentage: 1-5% tannic acid, 1-5% collagen, 50-55% polytetrahydrofuran, 25-30% isophorone diisocyanate, 5-10% chain extender, and 0.2-0.3% catalyst.

[0024] Furthermore, the chain extender is 1,4-butanediol.

[0025] Furthermore, the catalyst is dibutyltin dilaurate.

[0026] Furthermore, a method for preparing a composite polyurethane membrane having both antifouling and adsorption properties for divalent copper ions in seawater is provided, and the composite polyurethane membrane obtained is used in a seawater system.

[0027] Technical description: Conventional polyurethane has limited adsorption capacity for heavy metals in seawater. Based on polyurethane, the present invention uses plant extract tannic acid and collagen blended precipitate to solve the problem of tannic acid being easily soluble in water, and prepares an environmentally friendly green multifunctional composite polyurethane membrane.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) Both antifouling and adsorption properties

[0030] Polyurethane is prepared through polymer organic polymerization reaction and modified with tannic acid / collagen complex, so that the composite polyurethane film has both antifouling function and can effectively adsorb Cu(Ⅱ) ions, providing a double guarantee for solving the problems of marine biofouling and seawater copper ion pollution. Tannic acid and collagen modified polyurethane, while improving the adsorption performance of the original polyurethane, can further enhance the adsorption capacity of divalent copper ions because collagen is rich in amino groups, which helps to reduce the concentration of Cu(Ⅱ) in the marine environment.

[0031] (2) Solve the problem of tannic acid water stability

[0032] First, tannic acid and collagen are co-precipitated in water, and then the precipitate is grafted onto polyurethane, which successfully solves the problem of poor stability and solubility of tannic acid in water, and improves the stability and service life of the composite membrane.

[0033] (3) Easy operation and high production efficiency

[0034] The raw materials for preparing composite polyurethane films, such as tannic acid, collagen, polytetramethylenefuran, isophorone diisocyanate, chain extenders and catalysts, are all common chemical substances and are easy to obtain, which provides convenient conditions for industrial production and reduces production costs.

[0035] The preparation method has the advantages of being easy to operate, and each step is easy to control and implement. For example, in terms of reaction conditions, the stirring rate, heating rate, etc. are clearly specified, and it is easy to operate in the laboratory and industrial production. At the same time, the production efficiency is high, and the composite polyurethane film can be quickly prepared, which is conducive to large-scale production.

[0036] (4) Feasibility of industrial production

[0037] This preparation method provides a feasible technical route for the industrial production of composite polyurethane membranes. From the selection of raw materials to the design of the process, the actual needs of industrial production are taken into consideration. The product can be further processed to obtain products with different proportions and adsorption and antifouling effects, which will help promote the wide application of the composite membrane in actual production.

[0038] (5) Environmentally friendly and has broad application prospects

[0039] It provides new ideas and methods for reducing the concentration of divalent copper ions in the marine environment and reducing marine biofouling, which is of great significance for protecting the marine ecological environment. It has broad application prospects in seawater systems and can be applied to marine aquaculture, marine engineering and other fields, which helps to maintain the balance of marine ecology and the sustainable use of marine resources. DETAILED DESCRIPTION

[0040] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0041] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0042] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0043] Example 1

[0044] A composite polyurethane membrane with both antifouling and adsorption of divalent copper ions in seawater, characterized in that it comprises the following raw materials in weight percentage: 3% tannic acid, 3% collagen, 55.3% polytetrahydrofuran, 28.5% isophorone diisocyanate, 10% chain extender, and 0.2% catalyst;

[0045] The preparation method specifically comprises the following steps:

[0046] S1. Mix tannic acid and collagen in deionized water, wherein the mass volume ratio of tannic acid, collagen and deionized water is 10:10:100 g / mL. During stirring, the pH is controlled to be 7.0, the stirring rate is 100 rpm, and the stirring is performed for 1 h to allow the tannic acid and collagen to fully react to obtain a precipitate A.

[0047] S2. Add isophorone diisocyanate dropwise to polytetrahydrofuran at room temperature, continue stirring to react, the stirring rate is 200 rpm, the heating rate is 3°C / min, the temperature is maintained at 80°C after heating, the reaction time is 2.5h, and polyurethane B is obtained;

[0048] S3, continue to add chain extender, catalyst and precipitate A to polyurethane B, reflux and stir to react, the stirring rate is 200 rpm, the heating rate is 1°C / min, the temperature is maintained at 60°C after heating, the reaction time is 7h, and tannic acid / collagen composite polyurethane is obtained;

[0049] S4, pouring the tannic acid / collagen composite polyurethane of step S3 into a polytetrafluoroethylene mold while it is hot, leaving it at room temperature for two days to dry into a film, and then putting the obtained film into an oven and drying it at 40° C. for 20 hours to obtain a composite polyurethane film.

[0050] Example 2

[0051] A composite polyurethane membrane with both antifouling and adsorption of divalent copper ions in seawater, comprising the following raw materials in weight percentage: 5% tannic acid, 5% collagen, 54.8% polytetrahydrofuran, 25% isophorone diisocyanate, 10% chain extender, and 0.2% catalyst;

[0052] The preparation method specifically comprises the following steps:

[0053] S1. Mix tannic acid and collagen in deionized water, wherein the mass volume ratio of tannic acid, collagen and deionized water is 15:15:100 g / mL. During stirring, the pH is controlled to be 7.0, the stirring rate is 150 rpm, and the stirring is performed for 1.2 h to allow the tannic acid and collagen to fully react to obtain a precipitate A.

[0054] S2. Add isophorone diisocyanate dropwise to polytetrahydrofuran at room temperature, continue stirring to react, the stirring rate is 400 rpm, the heating rate is 5°C / min, the temperature is maintained at 80°C after heating, the reaction time is 2.5h, and polyurethane B is obtained;

[0055] S3, continue to add chain extender, catalyst and precipitate A to polyurethane B, reflux and stir to react, the stirring rate is 400rpm, the heating rate is 3℃ / min, the temperature is maintained at 60℃ after heating, the reaction time is 7h, and tannic acid / collagen composite polyurethane is obtained;

[0056] S4, pouring the tannic acid / collagen composite polyurethane of step S3 into a polytetrafluoroethylene mold while it is hot, leaving it at room temperature for two days to dry into a film, and then putting the obtained film into an oven and drying it at 50° C. for 24 hours to obtain a composite polyurethane film.

[0057] 1. Anti-biological attachment performance test

[0058] The present invention selects two typical bacteria, Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli), to evaluate the antifouling ability of the composite polyurethane film.

[0059] Ⅰ. Use liquid culture medium (Luria-Bertan) to culture the bacteria to be used. The main operation steps are as follows: Take 500mL of deionized water, 5g of tryptone, 2.5g of yeast extract and 5g of NaCl powder to prepare liquid culture medium, put the prepared liquid culture medium into a high-temperature steam sterilizer for high-temperature sterilization, and then cool to room temperature. Take 10μL of the strain and add it to 100mL of liquid culture medium, and put it in an incubator (the temperature is set to 37°C and the incubation time is 24 hours) for culture;

[0060] Ⅱ. Sterilize the composite polyurethane membranes of Examples 1 and 2 (sterilize with UV light for 30 minutes) and place them in a 100 mL conical flask. Dilute the cultured bacterial solution with liquid culture medium (dilute to 4×10 6 / mL), take 50mL of the diluted bacterial solution and add it to the above conical flask, seal the conical flask with aerobic culture sealing film. Then place the conical flask in an incubator for incubation (the temperature is set at 37°C and the incubation time is 24 hours);

[0061] III. Take out the sample from the liquid culture medium, separate the E. coli cells from the surface with 10 mL of LB liquid culture medium, collect 10 mL of LB liquid culture medium containing the separated E. coli cells and dilute it to 0.5% of the original;

[0062] IV. Evenly spread 10 μL of the diluted liquid culture medium on the surface of LB solid culture medium (500 mL of deionized water, 5 g of tryptone, 2.5 g of yeast extract, 5 g of NaCl powder, and 7.5 g of agar powder), then invert the coated culture dish and place it in an incubator for incubation (the temperature is set to 37°C and the incubation time is 24 hours).

[0063] During the test, three parallel samples were selected, and the diluted liquid culture medium corresponding to each sample was spread on the solidified LB agar plate five times. After the incubation, digital photos were taken, and the antibacterial efficiency (E) of the test sample was calculated according to the formula b ).

[0064]

[0065] Wherein, H1 is the number of colonies grown by the test sample on solid culture medium;

[0066] H2 is the number of colonies grown on solid medium of the control sample.

[0067] 2. Test method for adsorption performance of Cu(Ⅱ)

[0068] Take 100 ml of 100 mg / L Cu(II) solution, then put in 0.5 g of composite polyurethane membrane, shake on a shaker at 200 rpm / min, and conduct adsorption experiments with different contact times (10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120 min). The Cu(II) concentration at a certain time is measured using an ICP inductively coupled plasma spectrometer.

[0069] The adsorption amount of the polyurethane film at time t is calculated as follows:

[0070]

[0071] In the formula, C0 and Ct is the concentration of Cu(II) at the initial time and at time t, V(L) is the volume of the solution, and m(g) is the mass of the material.

[0072] The adsorption rate of polyurethane film is calculated as follows:

[0073]

[0074] In the formula, C0 and C t is the concentration of Cu(II) at the initial time and at time t.

[0075] The test results are shown in the following table:

[0076]

[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite polyurethane film having both antifouling and adsorption of divalent copper ions from seawater, characterized in that: The following steps are involved: S1. Blending tannic acid, collagen and deionized water to obtain a precipitate A; S2, copolymerizing polytetrahydrofuran and isophorone diisocyanate to obtain polyurethane B; S3, copolymerizing the prepared precipitate A with polyurethane B to obtain tannic acid / collagen composite polyurethane; S4. Pour the prepared tannic acid / collagen composite polyurethane into a polytetrafluoroethylene mold while it is hot, dry it naturally and then dry it in an oven to obtain a tannic acid / collagen composite polyurethane film.

2. The method for preparing a composite polyurethane film having both antifouling and adsorption properties of divalent copper ions in seawater according to claim 1, characterized in that: The specific steps include: S1. Mix tannic acid and collagen in deionized water, wherein the mass volume ratio of tannic acid, collagen and deionized water is (10-15):(10-15):

100. During stirring, the pH is controlled to be 7.0 so that the tannic acid and collagen react fully to obtain a precipitate A. S2. Add isophorone diisocyanate dropwise to polytetrahydrofuran at room temperature, continue stirring to react, and maintain the temperature at 80-85° C. after heating for 2-2.5 hours to obtain polyurethane B; S3, continue to add chain extender, catalyst and precipitate A to polyurethane B, reflux and stir to react, and keep the temperature at 60-70°C for 5-7h to obtain tannic acid / collagen composite polyurethane; S4, pouring the tannic acid / collagen composite polyurethane of step S3 into a polytetrafluoroethylene mold while it is hot, leaving it at room temperature for two days to dry into a film, and then putting the obtained film into an oven and drying it at 40-60° C. for 20-30 hours to obtain a composite polyurethane film.

3. The method for preparing a composite polyurethane film having both antifouling and adsorption properties of divalent copper ions in seawater according to claim 1, characterized in that: The stirring rate of S1 is 100-150 rpm, and the stirring time is 1-1.2 h.

4. The method for preparing a composite polyurethane film having both antifouling and adsorption properties for divalent copper ions in seawater according to claim 1, characterized in that: The stirring rate of S2 is 200-400 rpm, and the heating rate is 3-5°C / min.

5. The method for preparing a composite polyurethane film having both antifouling and adsorption properties of divalent copper ions in seawater according to claim 1, characterized in that: The stirring rate of S3 is 200-400 rpm, and the heating rate is 1-3°C / min.

6. A composite polyurethane membrane with both antifouling and adsorption of divalent copper ions from seawater, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5.

7. A composite polyurethane membrane having both antifouling and adsorption properties for divalent copper ions in seawater as claimed in claim 6, characterized in that: The invention comprises the following raw materials in weight percentage: 1-5% of tannic acid, 1-5% of collagen, 50-55% of polytetrahydrofuran, 25-30% of isophorone diisocyanate, 5-10% of chain extender and 0.2-0.3% of catalyst.

8. The composite polyurethane membrane having both antifouling and adsorption properties of divalent copper ions in seawater as claimed in claim 7, characterized in that: The chain extender is 1,4-butanediol.

9. The composite polyurethane membrane having both antifouling and adsorption properties of divalent copper ions in seawater as claimed in claim 7, characterized in that: The catalyst is dibutyltin dilaurate.

10. Use of the composite polyurethane membrane obtained by the method for preparing a composite polyurethane membrane having both antifouling and adsorption of divalent copper ions in seawater according to any one of claims 1 to 5 in a seawater system.

Citation Information

Patent Citations

  • Preparation method of copper adsorbant

    CN106040193A

  • Magnetic ceramsite adsorbent for removing heavy metal copper ions in water and preparation method

    CN115608340A